The STEM gap: Overcoming obstacles and incorporating women globally - Lohgheswary, N.; R, Leelavathi. (Edelweiss Applied Science and Technology, 2025)
This paper discussed two issues involving women in STEM. The first issue is why are women avoiding STEM fields. A framework illustrated that personal factors, environmental factors, and behavioural factors are the three factors that push away women from STEM. Personal factors include girls who are better in language skills and discourage them from choosing STEM subjects. Environmental includes the thought of STEM is highly factual and far away from the current trends. Behavioural factors include the aspirations of women to choose careers to support others. Connections, Opportunities, Growth Mindset, Stereotypes, Collaboration, and role models are ways to enhance women in STEM. Industry partnerships with educational institutions will increase female students’ interest in STEM. One way to deal with gender inequality is to work with young children using statements from the current statistics to start conversations in the classroom. The Science Olympiad and other national competitions have shaped the interests and skills of 21st-century female students. Educators and activists continue to influence the media, corporations, and educational institutions to present and recruit women in all STEM occupations. More women should join the STEM field to reduce the gender gap.